2015
DOI: 10.1097/ncc.0000000000000163
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Circadian Rhythms and Physical Activity With Objective Sleep Parameters in Lung Cancer Patients

Abstract: Adequate light-intensity physical activity can be an effective intervention to improve sleep quality in lung cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 47 publications
0
35
0
2
Order By: Relevance
“…It is possible that the dichotomy index is a more sensitive marker of perceived sleep function because it takes both daytime and nighttime activity into account. [21; 22; 26] Indeed, patients who complained of poor sleep allegedly suffered from consequences of unrestful sleep during daytime, and the circadian rest-activity rhythm was reported as a correlate to fatigue,[8; 25] an expected repercussion of altered nighttime sleep. [38]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the dichotomy index is a more sensitive marker of perceived sleep function because it takes both daytime and nighttime activity into account. [21; 22; 26] Indeed, patients who complained of poor sleep allegedly suffered from consequences of unrestful sleep during daytime, and the circadian rest-activity rhythm was reported as a correlate to fatigue,[8; 25] an expected repercussion of altered nighttime sleep. [38]…”
Section: Discussionmentioning
confidence: 99%
“…[22] In previous studies, I<O has been shown to be one of the most clinically relevant circadian parameters in terms of prognosis and correlation with health-related quality of life and symptoms. [18; 2326]…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, sleep quality can be objectively assessed through actigraphy: sleep disturbance is indicated by a total sleep time (TST) of ⩽6.5 h (Lacks and Morin, 1992), sleep efficiency (SE) of ⩽85% (Coates et al , 1982), sleep onset latency (SOL) of >30 min (Espie et al , 2001), or wake after sleep onset (WASO) of >30 min (Savard and Morin, 2001). Factors including age (Kim et al , 2000; Chen et al , 2015b), sex, marital status (Baiden et al , 2015), cancer stage, and anticancer treatments (Roscoe et al , 2007; Chen et al , 2015b), which can affect sleep quality, must be included in sleep quality assessments for cancer patients. Unstable rest-activity rhythms lead to sleep disturbance (Miaskowski and Lee, 1999; Berger et al , 2007), and non-small-cell lung cancer patients with disrupted rest-activity rhythms may experience poor sleep quality and insomnia (Levin et al , 2005).…”
mentioning
confidence: 99%
“…Supporting this notion is evidence that regular PA induces neurochemical changes that qualitatively and quantitatively improve sleep across patient populations [2729, 368372]. One RCT in sedentary adults with insomnia demonstrated that increasing PA to the level recommended in public health guidelines (≥150 min of moderate- to vigorous-intensity PA per week) improved sleep quality [28], whereas other studies demonstrated that adults who fail to achieve sufficient levels of PA incur sleep problems [372375].…”
Section: Circadian Rhythmicity and Physical Activitymentioning
confidence: 99%
“…PA alters the progression of MD neuropathology by optimizing the levels of neurotransmitters [13], neurotrophic factors [13, 14], beta-endorphins [15], cortisol [16, 17], and muscle-derived protein (peroxisome proliferator-activated receptor gamma coactivator 1- α [PGC-1 α ]) [18]. Moreover, regular PA optimizes processes involved in neurogenesis [19, 20], immune function [21, 22], stress regulation [23, 24], antioxidant defense [25, 26], circadian rhythms [2729], epigenetic modifications [30, 31], and the maintenance of telomere length [32–35]. …”
Section: Introductionmentioning
confidence: 99%